Antifungal activity of aloe vera gel towards the pathogenic fungus of papaya fruit - Mendy, T. K.; Misran, Azizah; Tengku Muda Mohamed, Mahmud; Ismail, S. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The aim of this research is to evaluate the inhibitory effect of aloe vera on the mycelia growth of five pathogenic fungi that caused spoilage in papaya fruits. In this experiment, two types of aloe vera extract; fresh aloe vera and food grade were used. Both of the extracts with different concentrations (0, 15 %, 25 %, and 50 % (v/v)) were tested against mycelium growth of five pathogenic fungi of papaya fruits (Fusarium sp., Aspergillus niger, Colletotrichum gloeosporioides, Lasiodiplodia theobromae and Rhizopus sp) that were isolated from papaya fruits.At 15 % concentration, fresh aloe vera effectively inhibited all the fungi as compared to food grade aloe vera. Analysis on the composition of the aloe vera demonstrated phenolic, flavonoid content and DPPH radical scavenging activity were found to be concentration dependent, with the fresh aloe exhibiting higher phenolic content, flavonoid and DPPH activity than the food grade aloe vera gel. The finding of present study concluded that both fresh and food grade aloe vera controlled the mycelia growth of major postharvest fungus of papaya fruit in vitro. Fresh aloe vera extract has a significant inhibitory effect on the fungus that caused spoilage in papaya and can be potentially used as edible coating to extend the shelf life of the fruits and vegetables.